Anti-biofilm and anti-inflammatory effect of a herbal nanoparticle mouthwash: a randomized crossover trial - Maísa CASARIN; Josiele PAZINATTO; Leandro Machado OLIVEIRA; Márcia Ebling de SOUZA; Roberto Christ Vianna SANTOS; Fabricio Batistin ZANATTA (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract Laboratory evidence has demonstrated the antimicrobial effect of Melaleuca alternifolia (MEL) against oral microorganisms. This randomized, double-blind, crossover clinical trial, compared the anti-biofilm and anti-inflammatory effects of MEL nanoparticles with 0.12% chlorhexidine gluconate (CHX) on biofilm-free (BF) and biofilm-covered (BC) surfaces. Before each experimental period, the participants refrained from all oral hygiene practices for 72 hours. The 60 participants were randomly assigned to professional prophylaxis in two quadrants (Q1-Q3 or Q2-Q4), and rinsed with MEL or CHX for four days. The Quigley & Hein plaque index (QHPI), gingival crevicular fluid (GCF) volume, and participants' perceptions were assessed. CHX showed significantly lower mean QHPI on BF (2.65 ± 0.34 vs. 3.34 ± 0.33, p < 0.05) and BC surfaces (2.84 ± 0.37 vs. 3.37 ± 0.33, p < 0.05). Intragroup comparisons indicated reductions in GCF in all the groups, with significant differences only for CHX on BF surfaces (p < 0.05). Intergroup comparisons revealed no significant differences (p > 0.05). Based on individual perceptions, CHX had better taste and biofilm control, but resulted in a greater change in taste. Nevertheless, MEL demonstrated anti-inflammatory effects similar to those of CHX. Further clinical trials testing different protocols, concentrations and follow-up periods are required to establish its clinical application.